Characteristics of unsupported alumina membrane prepared using sol-gel technique - M.R. Othman,; A.L. Ahmad; H. Mukhtar (Universitas Gadjah Mada, 2001)
A laboratory scale alumina membrane was prepared using sol-gel technique. Results from the experiment demonstrate that the addition of PVA is important for viscosity adjustment to determine the appropriate coating time if the membrane is required for coating on the porous support. The effects of varying PVA content and sintering temperature on the characteristics of the sintered membrane are discussed. In this work, a 2 volume % of PVA solution containing 4g of PVA in lOOml of water was discovered to be adequate to achieve appropriate porosity level and avoid cracks in the gel layer. It was also discovered that the sol viscosity essentially increased as the PVA addition was increased. On the contrary, the coating time decreased as PVA content in the sol was increased. Generally, the pore size of the membrane increased with the increase in PVA addition. The density of the membrane increased with increase in sintering temperature. The porosity level however, decreased as the temperature was increased. The pore size became greater and pore size distribution wider at higher sintering temperatures.